Complexes and bioenergy of invertebrates in oil-polluted gray-brown soils of Absheron - Ahmed, Pirverdi Samadov (International Journal of Advances in Applied Sciences, 2024)
Oil pollution negatively impacts not only the physicochemical and morpho-genetic parameters of soils but also the vital activity of soil biota-microorganisms and invertebrates. Studies have established that in the uncontaminated gray-brown soil of the Binagadi and Karadag massifs, the bulk of the invertebrate complex is gastropoda, insecta, tenebrionidae, and carabidae. In lightly oil-polluted biotopes, insecta, gastropoda, lithobiidae, tenebrionidae, carabidae, buprestidae, and woodlice of the genus hemilepstus occupy the leading place. The total number and biomass of invertebrates in uncontaminated biotopes of gray-brown soils of the Binagadi and Karadag massifs is 19.2 ind/m2, respectively; 26 gr/m2 and 20 ind/m2; 3.64 gr/m2. In slightly oil-contaminated biotopes, these indicators vary between 25.6 ind/m2, respectively; 3.5 gr/m2 and 12.8 ind/m2; 0.84 gr/m2. The energy accumulated in the mesofauna biomass in the slightly oil-polluted biotopes of the Karadag and Binagadi massif varies between 0.3268 gr/m2-1418.94 cal/m2 and 1.0468 gr/m2-5072.20 cal/m2, respectively. Thus, the reliability of the biogeocenoses is determined by the level and effective activity of soil organisms.